A Companion to Research in Education
XXIX, 606 p. 36 illus., 16 illus. in color.
Keywords: This volume offers a unique commentary on the diverse ways that educational inquiry is conceived, designed and critiqued. An international team of scholars examines cross-cutting themes of how research in education is conceptualised, characterised, contextualised, legitimated and represented. Contributions include specially commissioned essays, critical commentaries, vignettes, dialogues and cases. Each section discusses the significance of a complex terrain of ideas and critiques that can inform thinking and practice in educational research. The result is a thorough and accessible volume that offers fresh insights into the perspectives and challenges that shape diverse genres of research in education.